2016
DOI: 10.1371/journal.pone.0148854
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elevated Hemoglobin and Serum Protein on Vasovagal Reaction from Blood Donation

Abstract: We conducted a cross-sectional study to elucidate factors contributing to vasovagal reaction (VVR), the most frequent side effect following whole blood and apheresis donations. Complications recorded at the collection sites after voluntary donations by the Japanese Red Cross Tokyo Blood Center (JRC), in the 2006 and 2007 fiscal years, were analyzed by both univariate analysis and the multivariate conditional logistic regression model. Of 1,119,716 blood donations over the full two years, complications were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…One Japanese study recently noted that elevated hemoglobin and serum protein levels were indicators of higher rates of vasovagal reactions, which was similar to the findings in this study [20]. Although all study participants enrolled in this study had Hgb levels above the minimum eligibility criteria for donation (12.5 g/dl), surprisingly donors at the upper end of Hgb levels (>15 g/dl) were at the highest risk of contracting adverse events which raises a point of whether to set both a low and a high marginal limit of donation criteria to ensure donor safety.…”
Section: Resultssupporting
confidence: 89%
“…One Japanese study recently noted that elevated hemoglobin and serum protein levels were indicators of higher rates of vasovagal reactions, which was similar to the findings in this study [20]. Although all study participants enrolled in this study had Hgb levels above the minimum eligibility criteria for donation (12.5 g/dl), surprisingly donors at the upper end of Hgb levels (>15 g/dl) were at the highest risk of contracting adverse events which raises a point of whether to set both a low and a high marginal limit of donation criteria to ensure donor safety.…”
Section: Resultssupporting
confidence: 89%
“…Vasovagal syncope has been the main focus of blood donor safety and the risk factors for VVRs have included blood donation for first-time donors, young age, female sex, lower BMI, short sleep time, and apheresis donation (1). In this case, we believe that first time plasma donation was an important cause of the patient's VVR.…”
Section: Discussionmentioning
confidence: 80%
“…Although blood donation is considered safe, the prevalence of adverse reactions, such as vasovagal reactions (VVR), hematomas, citrate reactions, and nerve injuries, is approximately 1% (1). However, ischemic colitis has not been recognized as an adverse reaction of blood donation.…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by research done by France CR., et al that showed 56.7% of non fearful blood donors had no vaso-vagal reaction after blood donation as compared to the 33.2% of fearful donors who experienced fainting (26). A study conducted by Japanese Red Cross Tokyo Blood Centre (JRC) in 2007 shows that most frequent side effect following whole blood donation is vaso-vagal reaction (VVR), 67% cases of VVR were reported for 1.18% blood donation (27). The results of a study done by Dilsad S.,et al showed that anxiety about the procedure (fear of fainting ) leads to avoidance of blood donation (15).…”
Section: Factors Refraining Medical Students From Blood Donation; a Tmentioning
confidence: 99%
“…Holland PV reviewed that risk of HCV infection by transfusion is 1 in 3,300 (16). A study conducted at Karachi shows that among 148268 total donors, 1.03% donors were reactive for HIV and Treponema pallidum of which 99.94% were males of younger age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years (29) Since the subjects of our research are medical students so time management is very important. Our result showed that 21.57% of students were not donating blood because of lack of time.…”
Section: Factors Refraining Medical Students From Blood Donation; a Tmentioning
confidence: 99%